1996
DOI: 10.1037/0735-7028.27.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of APPIC predoctoral psychology internship application forms.

Abstract: Internship application forms sent by officials from 81 Association of Professional Psychology Internship Centers (APPIC) predoctoral internship sites accredited by the American Psychological Association were examined to identify common items for the purpose of developing a single standardized questionnaire. Questions found on at least 20% of 50 application forms composed a master list against which items on the remaining 31 validation applications were compared. The final revision of the standardized questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Another breakthrough in the selection process occurred when APPIC adopted a uniform application, the APPIC Application for Psychology Internship (AAPI). Holiday and McPhearson (1996) described the development of the first version of this long overdue innovation. Not only has the uniform application benefited students but, potentially, it could provide a stable database for ongoing studies of internship related phenomena, although this latter benefit has yet to be fully utilized.…”
Section: The Intern Selection Processmentioning
confidence: 99%
“…Another breakthrough in the selection process occurred when APPIC adopted a uniform application, the APPIC Application for Psychology Internship (AAPI). Holiday and McPhearson (1996) described the development of the first version of this long overdue innovation. Not only has the uniform application benefited students but, potentially, it could provide a stable database for ongoing studies of internship related phenomena, although this latter benefit has yet to be fully utilized.…”
Section: The Intern Selection Processmentioning
confidence: 99%
“…One of the most substantial improvements occurred when APPIC adopted an optional standardized application form, the APPIC Application for Psychology Internship (AAPI), in the 1997–1998 internship year. The AAPI has eliminated much of the redundancy faced by previous intern applicants, but perhaps more important, it demonstrates that standardization is possible even in the diverse profession of psychology (Holaday & McPhearson, 1996). Data from the AAPI are already providing feedback to internship directors, directors of clinical training, and others because benchmarks are emerging with regard to some universally accepted competencies within and across programs.…”
Section: Progress In the Internship Processmentioning
confidence: 99%
“…In addition, training directors supported APPIC's development of a universal application form that APPIC used during the 1998 selection process. Holiday and MacPhearson (1996) described the issues involved in the development of a uniform application form and concluded that a standardized form would benefit students. The Association of Psychology Graduate Students (S. Lopez, personal communication, November 4, 1998) indicated their strong support for a universal application form, and the results of our study support APPIC's use and refinement of the APPIC application for psychology internships.…”
Section: Satisfaction With Selectionmentioning
confidence: 99%